2022
DOI: 10.2147/dmso.s377901
|View full text |Cite
|
Sign up to set email alerts
|

Unhealthy Dietary Patterns Increased Risks of Incident Obesity: A Prospective Cohort Study in Southwest China

Abstract: Purpose Few studies have explored the associations between diet patterns and incident obesity in China. This study aimed to explore associations between dietary patterns and incident obesity in a prospective community-population cohort in Southwest China. Patients and Methods Totally, 5742 adult residents from Guizhou province were eligible for this analysis. Demographic characteristics, lifestyle, history of chronic diseases, and dietary patterns measured by hundred-it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 54 publications
0
2
0
Order By: Relevance
“…A large cohort study in China investigated the risk of cancer in five major autoimmune diseases. 31 The results showed that the standardized incidence ratio (SIR) for cancers in patients with RA was 3.99 (95% CI 2.40-3.65). RA patients had no significant difference in site-specific SIRs, suggesting a wide distribution of cancer sites after 15 years since the diagnosis of RA.…”
Section: Malignanciesmentioning
confidence: 99%
“…A large cohort study in China investigated the risk of cancer in five major autoimmune diseases. 31 The results showed that the standardized incidence ratio (SIR) for cancers in patients with RA was 3.99 (95% CI 2.40-3.65). RA patients had no significant difference in site-specific SIRs, suggesting a wide distribution of cancer sites after 15 years since the diagnosis of RA.…”
Section: Malignanciesmentioning
confidence: 99%
“…In southwestern China, factors such as geographical environment contribute to a preference for high-fat, high-salt, and spicy foods, which may increase the risk of chronic diseases [ 17 , 18 ]. Furthermore, the prevalence of chronic non-communicable diseases, such as diabetes, cardiovascular diseases, and obesity, is relatively high in southwestern China [ 19 , 20 , 21 ]. Previous research has shown that individuals’ diet knowledge influences their food choices, which in turn are influenced by their attitudes toward health [ 22 ].…”
Section: Introductionmentioning
confidence: 99%